Biodegradability of nonwoven flax fiber reinforced polylactic acid biocomposites. Issue 11 (15th January 2014) - Alimuzzaman, Shah; Gong, R.H.; Akonda, Mahmudul
<x xml:space="preserve">Abstract</x> Biocomposites of flax reinforced polylactic acid (PLA) were made using a new technique incorporating an air‐laying nonwoven process. PLA and flax fibers were mixed and converted to the webs in the air‐laying process. Prepregs were then made from the fiber webs by thermal consolidation. The prepregs were finally converted to composites by compression molding. This study was investigated the biodegradability and water absorption properties of the composites. The composites were incubated in compost under controlled conditions. The percentage weight loss and the reduction in mechanical properties of PLA and biocomposites were determined at different time intervals. It was found that with increasing flax content, the mechanical properties of the biocomposites decreased more during the burial trial. The increasing of flax content led to the acceleration of weight loss due to preferential degradation of flax. This was further confirmed by the surface morphology of the biodegraded composites from scanning electron microscope image analysis. Morphological observations indicated severe disruption of biocomposites structure between 60 and 120 days of incubation. POLYM. COMPOS., 35:2094–2102, 2014. © 2014 Society of Plastics Engineers